lg (x+2) + lg (x-2) = lg ( 5x+ 10)

0 голосов
154 просмотров

lg (x+2) + lg (x-2) = lg ( 5x+ 10)


Алгебра (20 баллов) | 154 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

ОДЗ:

x + 2 >0

x > - 2

x - 2 > 0

x > 2

5x + 10 > 0

x > -2

lg(x+2) + lg(x-2) = lg(5x + 10)

lg((x+2)(x-2)) = lg(5x + 10)

x^2 - 4 = 5x + 10

x^2 - 4 - 5x - 10 = 0

x^2 - 5x - 14 = 0

D = sqrt(25 + 56)

D = 9

5 +- 9/2

x1 = 7; x2 = -2

Второй корень не входит в ОДЗ.

Ответом уравнения будет точка {7}

Ответ: {7}

(4.1k баллов)
0 голосов

lg(x*2-4)=lg(5x+10)

x*2-5x-14=0

D=25-16=9

x1=(5+3)/2=4

x2=1

 

 

 

 

 

 

 

 

(189 баллов)